She’s Having an Episode: Patricia Williams and the Writing of Damaged Life - Berlant, Lauren (Columbia Journal of Gender and Law, 2014)
About a work as intense and theatrical as this one, it might be odd to claim that On Being the Object of Property struggles with exemplarity by dedramatizing narrative into episode, epic into moment, and structure into gestures that convey intensities of need for the world to be a certain way. But this diminishing process—the episode as cooling chamber—is key to the work’s aesthetic, political, and ethical ambition to give subordinated bodies in the present a shot at not having the past reproduced in the contemporary nervous system. The interruption by aesthetic virtuality, by counter-form, is key to her strategy—not method—here. (It is not a method insofar as it is inimitable, not-prescriptive, and creative.) But the essay is not only affirmative about the process of aggressively remediating the world. For the labor of imagining a way to build a better good life out of the space of converged negativities and tender attachments is terribly costly, affectively. “As if a slaved or owned psyche could ever be reconciled with mental health,” Williams writes with dry, ironic flatness, noting additionally that cohabiting with her knowledges induces “a schizophrenia of biblical dimension . . . with all the baggage that that connotes.”